Resocialization Of Convicts in The Czech Republic: The Role of The Prison System in Promoting Reintegration into Society - Vlach, František; Stárek, Lukáš (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
The article focuses on the execution of imprisonment in the Czech Republic, its objectives and responsibilities in the context of promoting the reintegration of convicted persons into society. The main mission of the prison system is not only to ensure the safety of society and protection from offenders, but also to provide systematic social support and penitentiary care. Specially trained staff help convicts to understand their behaviour, the reasons for breaking the law and to acquire new moral standards, skills and knowledge. This approach emphasises the transformation of convicts, with the aim of reducing the risk of reoffending and facilitating their return to society as active, independent and contributing members. The practical and social-adaptive skills developed during their sentence are crucial for their successful re-socialisation and minimising the risks associated with re-offending. The study offers insight into the principles and practices of the Czech penitentiary system, with an emphasis on its rehabilitative and preventive functions. The current Russo-Ukrainian war has caused an influx of Ukrainian refugees, including those who may have committed crimes in the Czech Republic. This situation places increased demands on the prison system, which must respond not only to the general needs of convicts, but also to the specific challenges arising from their cultural, legal and social context.